MOOCs and access to higher education by South African underprivileged learners - Mabhele, Mncedisi Chris (Department of Information Systems, 2025)
Background: Underprivileged South Africans struggle to access higher education for various reasons. Higher education potentially increases opportunities for the underprivileged to improve their socio-economic conditions. Higher education MOOCs have been revolutionary in providing quality higher education courses to the masses across the world with low barriers to entry and low cost. MOOCs could provide an alternative for underprivileged South Africans to access higher education. The purpose of the research: The main objective of this study is to identify and generate new and alternative perspectives on access to higher education by the underprivileged when assisted by the inclusion of MOOCs. To this end, this study discusses the role of MOOCs in reducing the barriers to access of higher education by underprivileged learners. Design/methodology/approach: This study employed mixed method approach (qualitative and quantitative methods). Initially, 25 one-on-one interviews with South Africa based participants were conducted online to gain insights and views on the topic. The results were analysed using thematic analysis. Subsequently, 116 South Africa based participants responded to a survey informed by the results from the initial interviews. The results were statistically analysed using regression analysis. Findings: The findings demonstrate that the underprivileged face many challenges in accessing higher education, including affordability, limited spaces within institutions and high entry requirements. The study further demonstrates that MOOCs can be used to address these challenges. However, challenges such as access to ICT, lack of role models and career guidance, low standard of basic education and not being academically prepared may need to be addressed through other means. Research contribution: This study adds to perspectives on the use of MOOCs to increase access to higher education by the underprivileged learners. Additionally, this study has the potential in creating new knowledge for underprivileged individuals to better leverage MOOCs in improving their chance to better life prospects. Lastly, this study can influence policy makers and higher education leadership in better using MOOCs in the quest for creating a more educated workforce.